A study on sources of stress among secondary school teachers at Kota Samarahan / Connelia Dublin and Ivy Jugah - Dublin, Connelia; Jugah, Ivy (2006)
According to recent international research, Special Educational Needs (SEN) teachers serve one of the most stressful occupations. The topic of this study is to identify the sources of stress among secondary teachers at Kota Samarahan. It aims to determine the impacts of stress faced by the secondary school teachers towards their job performance, health and students’ performance. Besides that, the purpose of this study is to identify the appropriate solutions in order to reduce stress. The method used to collect the data was through personally administrated questionnaires and the sample size of the study was 120 respondents. The outcome of the study indicated that teaching workload is the main source of stress and it result in headaches and migraines, unmotivated to work hard and as well as reduce the students’ academic performance. Therefore, respondents have come out with some solutions and most of them suggested that, they should focus on core business that is teaching and reduce the outdoor activities besides teaching.